A Case Study on Transition from Scrum to Kanban and Its Impact on Productivity and Collaboration - Abdelmalek Mohamed, Bassam Adel; Kučera, Jan; Malcová, Dana; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2025)
Agile methodologies are central to modern software development, yet time-boxed frameworks like Scrum present significant challenges for teams operating in reactive, maintenance-mode environments. This necessitates an empirical investigation into alternative, flow-based systems. This thesis aims to analyse and evaluate the impact of a transition from Scrum to Kanban on team productivity and collaboration within software maintenance teams. A mixed-methods, embedded multiple-unit case study was conducted over a six-month period, examining seven software development teams within a single organisation. Quantitative performance data was extracted from Jira for five teams that transitioned to Kanban and two control teams that remained on Scrum. This was triangulated with qualitative data from semi-structured interviews with team leadership. The findings demonstrate a significant and positive impact for the transitioning teams, which experienced an average increase in monthly ticket throughput of +28.4%, while the Scrum teams’ performance remained stable. The qualitative data reveals that this improvement was driven by Kanban's ability to better handle the unpredictable flow of work, though the transition was not without challenges. One team experienced an initial productivity dip attributed to tooling and cultural factors, highlighting the critical role of leadership and change management. This study concludes that for maintenance-mode work, Kanban is a demonstrably more effective framework than Scrum. The findings provide strong evidence that Agile methodology selection should be context-dependent, aligning the process to the nature of the work to maximise team productivity and responsiveness.
Vedoucí práce: Jan Kučera
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby
Způsob přístupu: Internet
Keywords: management of business informatics [obor dipl. práce]; diplomové práce; master's theses